Accountability for the Crimes Against Civilians Committed During the Armed Conflict in Ukraine - Głogowska-Balcerzak, Anna (Acta Universitatis Lodziensis. Folia Iuridica, 2024)
The article explores the question of crimes committed against the civilian population during the war in Ukraine and the possible ways of bringing to justice those responsible. A full-scale aggression launched by Russia has caused death and widespread suffering of thousands of Ukrainian civilians and combatants. The article focuses on the events following 24th February, 2022, bearing in mind that the conflict had started much earlier – with the illegal annexation of Crimea and the beginning of fighting in eastern part of the Ukraine in 2014. After introductory remarks in the first section, the second part of this article will be focusing on different acts constituting war crimes that were committed during the war in Ukraine, and the third part will address existing accountability mechanisms and briefly discuss the advantages and disadvantages of each of them.